2014 IEEE International Parallel &Amp; Distributed Processing Symposium Workshops 2014
DOI: 10.1109/ipdpsw.2014.183
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio-Based Selection of Robust Dynamic Loop Scheduling Algorithms Using Machine Learning

Abstract: The execution of computationally intensive parallel applications in heterogeneous environments, where the quality and quantity of computing resources available to a single user continuously change, often leads to irregular behavior, in general due to variations of algorithmic and systemic nature. To improve the performance of scientific applications, loop scheduling algorithms are often employed for load balancing of their parallel loops. However, it is a challenge to select the most robust scheduling algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…To address this situation, Sukhija et al proposed an approach that uses supervised machine learning techniques to predict the most robust loop scheduling strategy for a target application/platform [11]. To address this situation, Sukhija et al proposed an approach that uses supervised machine learning techniques to predict the most robust loop scheduling strategy for a target application/platform [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this situation, Sukhija et al proposed an approach that uses supervised machine learning techniques to predict the most robust loop scheduling strategy for a target application/platform [11]. To address this situation, Sukhija et al proposed an approach that uses supervised machine learning techniques to predict the most robust loop scheduling strategy for a target application/platform [11].…”
Section: Related Workmentioning
confidence: 99%
“…With this emerging variety of loop scheduling strategies, the task of selecting the most adequate one for a given application becomes challenging. To address this situation, Sukhija et al proposed an approach that uses supervised machine learning techniques to predict the most robust loop scheduling strategy for a target application/platform . They showed that their proposed approach (i) enables the selection of the most robust loop scheduling algorithm that satisfies a user‐specified tolerance on the given application's performance and (ii) offers higher guarantees regarding the performance of the application using the automatically selected loop scheduling algorithms, when compared with the performance of the same application using an empirically selected loop scheduling algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…In earlier work [3], a theoretical foundation of measuring the resilience value of a set of DLS methods with respect to variation in the processor failures has been described. In the latest related work [4], the flexibility analysis of DLS techniques in the presence of fluctuating system load for scheduling scientific applications onto computing systems was performed. To the best of our knowledge, this is the first work to analyze the resilience of the DLS algorithms using various combinations of problem sizes, system sizes and different types of application and systemic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It provides ready to use application programming interfaces (APIs) to represent applications and computing systems through different interfaces: MSG (SG-MSG), SimDag (SG-SD), and SMPI (SG-SMPI). SG uses a simple and fast CPU computation model and verified and more complex network models [18], which render it well suited for the study of computationallyintensive parallel and distributed scientific applications.Various studies have used SG to evaluate the performance of applications with DLS techniques in different scenarios [12,10]. To attain high trustworthiness in the performance results obtained with SG, the implementation of the nonadaptive DLS techniques in SG-SD has been verified [19] by reproducing the results presented in the work that introduced factoring [5].…”
mentioning
confidence: 99%
“…Various studies have used SG to evaluate the performance of applications with DLS techniques in different scenarios [12,10]. To attain high trustworthiness in the performance results obtained with SG, the implementation of the nonadaptive DLS techniques in SG-SD has been verified [19] by reproducing the results presented in the work that introduced factoring [5].…”
mentioning
confidence: 99%